심전도신호 샘플링 주파수에 따른 R파 검출 최적 문턱치 설정 - 조익성(Ik-sung Cho); 권혁숭(Hyeog-soong Kwon) (한국정보통신학회논문지, 2017)
It is difficult to guarantee the reliability of the algorithm due to the difference of the sampling frequency among the various ECG databases used for the R wave detection in case of applying to different environments. In this study, we propose an optimal threshold setting method for R wave detection according to the sampling frequency of ECG signals. For this purpose, preprocessing process was performed using moving average and the squaring function based the derivative. The optimal value for the peak threshold was then detected according to the sampling frequency by changing the threshold value according to the variation of the signal and the previously detected peak value. The performance of R wave detection is evaluated by using 48 record of MIT-BIH arrhythmia database. When the optimal values of the differential section, window size, and threshold coefficient for the MIT-BIH sampling frequency of 360 Hz were 7, 8, and 6.6, respectively, the R wave detection rate was 99.758%. R파 검출에 사용되는 여러 심전도 데이터베이스는 샘플링 주파수의 차이로 인해 서로 다른 환경에 적용할 경우 성능에 변화가 많아 알고리즘의 신뢰도를 보장하기 어렵다. 본 연구에서는 심전도신호의 샘플링 주파수에 따른 R파 검출의 최적 문턱치 설정 방법을 제안한다. 이를 위해 미분 기반의 이동평균과 제곱합수를 이용하여 전처리를 수행하였다. 이후 샘플링 주파수에 따라 피크 문턱치에 대한 최적 값을 검출하였다. 문턱치 단계는 신호의 변화와 이전 검출된 피크 값에 따라 문턱치를 변경함으로써 최적의 성능을 나타내는 값을 선정하는 과정으로 실험하였다. 제안한 방법의 우수성을 입증하기 위해 부정맥 데이터베이스 레코드를 대상으로 실험한 결과 MIT-BIH 샘플링 주파수 360Hz에 대한 미분 구간($N_d$), 윈도우 사이즈(N), 문턱 계수($p_{th}$)의 최적 값은 각각 7, 8, 6.6일 때 R파 검출율은 99.758%의 우수한 성능을 나타내었다.